Predicting teacher likelihood to use school gardens: A case study. Issue 2 (2nd April 2016) - Kincy, Natalie; Fuhrman, Nicholas E.; Navarro, Maria; Knauft, David
ABSTRACT: A quantitative survey, built around the theory of planned behavior, was used to investigate elementary teachers' attitudes, school norms, perceived behavioral control, and intent in both current and ideal teaching situations toward using gardens in their curriculum. With positive school norms and teachers who garden in their personal time, 77% of teachers' current intent to use school gardens was explained through backward linear regression. School gardens are more likely to be successful if teachers who garden in their personal time can serve as mentors to other teachers and promote positive norms and attitudes toward using gardens in the curriculum.